Sea surface temperature and surface seawater oxygen isotope composition reconstructions for sediment core I106 - Yiping Yang; Lanlan Zhang; Liang Yi; Zhengyao Lu; Fuchang Zhong; Wan Sui; Rong Xiang (PANGAEA, 2023)
We present sea surface temperature and oxygen isotopes in a sediment core I106 (6°14'49.76''N, 90°00'1.04''E; 2,910 m water depth) from the tropical East Indian Ocean, which provide new insights into the variability of tropical precipitation belt in Asian Monsoon region during the last deglaciation. The age model for the core is constrained by 17 AMS radiocarbon ages based on mixed planktonic foraminiferal samples. Mg/Ca derived sea surface temperature reconstructions based on Globigerinoides ruber (s. s., white) increased rapidly at about 19.5 ka, which is consisted with Mg/Ca-SST records in other cores in the tropical East Indian Ocean. Ice-volume corrected d18O seawater (d18Osw) exhibited a remarkable decline during the early Heinrich Stadial 1 (about 18.3-16.3 ka), and an increase during the late Heinrich Stadial 1 (16.3-14.7) ka. We attribute the decline of d18Osw in north of Equator from Asian Monsoon region to a contracted tropical precipitation belt during the early Heinrich Stadial 1.